TUGAS POKOK DAN FUNGSI (TUPOKSI) SATUAN POLISI PAMONG PRAJA (SATPOL PP) TENTANG PERATURAN DAERAH NO 15 TAHUN 2005 DI KOTA PONTIANAK - Doewiono Sasputro E.01106048 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article was triggered by desire to know the enforcement of regulations done by Satpol pp Pontianak City to regulation No. 15/2005 about gaming kite. Formulation problem of this research is "How Implementation Enforcement Regulation No. 15/2005 about gaming kite by municipal police in the district of  Pontianak City". As for the purpose of this research is to identify and explain the process of enforcement of regulations done by Satpol pp Pontianak City the regulation No. 15/2005 about gaming kite. A method of research here the use writers descriptive the kind of research and engineering data used in this research is observation, techniques interview documentation, the engineering data qualitative analysis writer descriptive used technique which has been collected data qualitative tillable and analyzed.From the results of analysis showed that the implementation of the enforcement regulation No. 15/2005 which done by Satpol pp to the communities in the district of Pontianak city has been qualified by principal and functions of municipal police are already stipulated in the regulations No. 10 / 2010. Enforcement of regulations done by Satpl pp Pontianak city razia  the form field and provide outreach to the community that netted rajia about the regulation No. 15/2005. There are still many people who do not care about these regulations and the absence of regular razia conducted Pontianak city municipal police in enforcing these regulations constitute barriers to the implementation of the enforcement of regulation No 15 / 2005. Keywords: enforcement of regulations and monitoring implementation of regulation number 15/2005 by the municipal police Pontianak city.